Standardization of Hinguvadhi Ghrita W.S.R Pharamacmaceutico Analytical Study - Dr.G.Kavitha,; Dr.Sadhana Misar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: In the present era, there is a need for examine the process of systematic research methodology and to provide genuine finding of various ayurvedic formulation mentioned in ayurvedic classics for the acceptance. Objective: To Standardize Hinguvadhi Ghrita on various parameter to assure its safety and efficacy w.s.rpharmaceutico analytical Study. Method: Hinguvadhi Ghrita was analyzed for its organoleptic physico-chemical features and screened for phyto-constituents as well as its chromatographic analysis. Result: The standardization and pharamaceutic analytical study of the ghrita helps to lay safety and efficacy of the ayurvedic formulation, hinguvadhi Ghrita. Conclusion: The analytical methodology in specific basis for research in ayurvedic formulation will facilitate the researchers to set quality standards as well as parameters to fulfill the requirement of therapeutic efficacy, safety and purity of ayurvedic ghee formulation. Hence, in this present study, it has been decided to standardize Hinguvadhi Ghrita.